Using Environmental Vocabulary to Compose Poems - Katili, Adriansyah Abu; Mahmud, Muzdalifah (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
This is an article about a community service activity conducted by the author at SMP Negeri 3, Gorontalo City. The goal of this activity was to improve the vocabulary skills of junior high school students and foster their creativity in language. The method of the activity was to introduce vocabulary for each object in nature. Then, they were guided to compose a simple poem using the vocabulary they had learned. They then wrote the poem in their notebooks, keeping it as a memory and study resource. As a result, they were able to master vocabulary and compose it into a simple poem.